Response-Dependent and Reduced Treatment in Lower Risk Hodgkin Lymphoma in Children and Adolescents, Results of P9426: A Report from the Children’s Oncology Group - Tebbi, Cameron K (2012)
BACKGROUND: Hodgkin lymphoma is highly curable but associated with significant late effects. Reduction of total treatment would be anticipated to reduce late effects. This aim of this study was to demonstrate that a reduction in treatment was possible without compromising survival outcomes. METHODS: Protocol P9426, a response-dependent and reduced treatment for low risk Hodgkin lymphoma (stages I, IIA, and IIIA(1)) was designed in 1994 based on a previous pilot project. Patients were enrolled from 10/15/1996 to 09/19/2000. Patients were randomized to receive or not receive Dexrazoxane and received 2 cycles of chemotherapy consisting of Doxorubicin, Bleomycin, Vincristine, and Etoposide. After 2 cycles, patients were evaluated for response. Those in complete response (CR) received 2550 cGy of involved field radiation therapy (IFRT). Patient with partial response or stable disease, received 2 more cycles of chemotherapy and IFRT at 2550 cGy. RESULTS: There were 294 patients enrolled, with 255 eligible for analysis. The 8 year event free survival (EFS) between the Dexrazoxane randomized groups did not differ (EFS 86.8 + 3.1% with DRZ, and 85.7 + 3.3% without DRZ (p=0.70). Forty five percent of patients demonstrated CR after two cycles of chemotherapy. There was no difference in EFS by histology, rapidity of response, or number of cycles of chemotherapy. Six of the eight secondary malignancies in this study have been previously reported. CONCLUSIONS: Despite reduced therapy and exclusion of most patients with Lymphocyte Predominant histology, EFS and overall survival are similar to other reported studies. The protocol documents that it is safe and effective to reduce therapy in low risk Hodgkin lymphoma based on early response to chemotherapy with rapid responding patients having the same outcome as slower-responding patients when given 50% of the chemotherapy.